Effect of Styrene-Butadiene Rubber Electrolytes Modified with BaCl2, MoCl2 and Active Carbon - Borowski, Tomasz (Asian Journal of Chemistry, 2010)
Styrene-butadiene rubber (SBR), as a solvent and repository of electric charges, gain these properties after adding to methanolic solution of BaCl2 or MoCl2 and active carbon by styrene-butadiene rubber. Electrical conductivity of SBR-active carbon system with added BaCl2 or MoCl2 equals to 10-5 to 10-6 S cm-1 at 293 K and a frequency of 10 kHz. The examined electrolytes were tested for the frequency range of 1 to 25 KHz. These polymer electrolyte systems may find their application as materials for anticorrosive and antielectrostatic protection of fuel or hazardous material tanks.